HOW CAN BOARD DIVERSITY PROMOTE CORPORATE INNOVATION? : A SYSTEMATIC LITERATURE REVIEW - Prithaningtyas, Arvianti; Windijarto, Windijarto (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2023)
Corporate innovation plays a crucial role in companies to remain sustainable in the future. Companies can also encourage the economic strength of a country. Innovative companies can be competitive in the market by improving marketing strategies and product innovation. Therefore, they can improve company performance. The board of directors has the authority to make strategic decisions to determine company performance. Based on the results of collecting 59 pieces of literature and then analyzing them, the researchers can conclude that various board characteristics such as board gender, foreign board, and board age can influence companies to innovate. Female directors can provide valuable insight, knowledge, and skills for companies to innovate to survive in the future. Foreign boards with cross-border knowledge and international relations can implement it into companies to innovate. Young directors have a much more risk appetite and are creative in trying new things.